On ergativization of intransitive verbs - Macková, Hana (2007)
The topic of my thesis are what Davidse (1998) calls ergative causatives of intransitive verbs, i.e. a subtype of causative constructions, which are built from primarily intransitive verbs and have two animate participants. These constructions are called by other various names such induced action causatives (Levin), causative accomplishment movement verbs (Van Valin) or double agentive causatives. This construction is a rather restricted phenomenon in the English language and there exist various conditions on its use. In the existing literature one still finds a number of unresolved questions and disputes. In my thesis, I will try to examine closely the semantic and syntactic structure of this construction type, I am going to look at its participants and at the particular type of verbs entering this causative type. These constructions occur only with limited set of verbs, especially manner of motion verbs. In her book, Levin (1993) introduces various subgroups of verbs, some of which .